Foundations of mental health care - Morrison-Valfre, Michelle (Elsevier/Mosby, 2013)
Increase your awareness and understanding of a holistic view of mental health care with this book for nurses and other health care professionals. Each chapter covers a specific psychological or psychosocial problem as well as the most current interventions and treatments. This edition features full-color illustrations, updated drug information, and a chapter on complementary and alternative therapies, in addition to more case studies to help you apply the content to real life. This solid background in mental health is just what you need to work comfortably with clients who exhibit both effective and maladaptive behaviors.